The Impact Of Independent Curriculum On Improving Students' Soft Skills: A Case Study In The Economic Education Study Program - Dearlina Sinaga; Nova Yunita Sari Siahaan; Sarina Artalina Sihombing (Jurnal Mamangan, 2023)
The problem in this study is to determine the impact of the independent curriculum on improving students' soft skills with a sample of 65 students. The research method in this study is used with descriptive research with a survey method The research instrument is used for data collection that is useful for researching populations and samples that have been determined. The data from this study must be quantitative data or statistical data in order to test the hypothesis that has been determined. The nature of this research is explanatory. This explanatory strategy is often referred to as a correlational research strategy (linking one variable with a variable of one to the other. The purpose of this study is to find out the improvement of Student Soft Skills in the Economics Education Study Program as an impact of the implementation of MBKM. Based on the analysis of data obtained during the distribution of questionnaires to students of Stambuk Economic Education 2020, 2021, 2022 who studied using the Independent curriculum. After data processing, there is a significant influence between variables X and Y as evidenced by the significance value in table 4.6 on the form of learning activities of the Independent curriculum with sig. = 0.05 and sig. t test = 0.000. So sig. = 0.05 ≥ sig. test T = 0.000. So there is an influence from the treatment given, namely the soft skills of students. With Tcount = 2.38 and Ttable = 2.49, then Tcount < Ttable. So it can be concluded that there is a significant influence between X and Y. with an average student score of 68 with a frequency of 12. Basically, the main purpose of this study is to find out how the impact of the independent curriculum on the impact of the independent curriculum: a case study in the economic education study program. Therefore, it can be concluded that there is a significant influence on the impact of the Independent curriculum (X) and the impact of the Independent curriculum (Y).